Examining the Development of Corporate Governance, the Process of Implementation and Board Composition: A Comparative Study of three countries: the United Kingdom, the United States and Japan - Muirhead, Robert (2010)
Abstract: When contemplating the nature of this research project I felt it appropriate to immerse myself in a topic which was not widely covered by the MSc in International Business. I felt that beyond the core modules of teaching there was still a vast array of important topics which affect businesses on a day-to-day basis. One of these topics, I learnt, was the role of corporate governance. As a topic corporate governance is vast and expansive, encapsulating a number of corporate disciplines while performing an important role in the regulation of a number of corporate disciplines. I felt it was important to refine my research to individual elements of governance and it is here that I chose to study the development and implantation of governance. Significant discussion is also given to board composition and the roles and responsibilities of executive and non-executive directors. The board of directors performs a number of important roles and responsibilities for corporate businesses which have recently become regulated by various codes of best practice and legislation. After consulting some sources I soon learned that governance is a topic which is far reaching yet is applied differently across the world. It was then that I opted to undertake a comparative study, comparing the governance systems in place in the UK, the United States and Japan.